Prevalence, association and correlation of frailty with sociodemographic and health-related factors among outpatient elderly persons: A cross-sectional study - Uchenna Cosmas Ugwu; Osmond Chukwuemeka Ene (Elsevier, 2024)
Background/objectives: Frailty is a significant clinical and public health concern. This study determined the prevalence, association and correlation of frailty with sociodemographic and health-related factors among out-patient elderly persons. Methods: A cross-sectional survey was conducted in tertiary healthcare facilities in Southeastern geopolitical zone of Nigeria from March 2023 to May 2023. A total of 500 elderly persons were conveniently surveyed. Data were collected using an adapted instrument called Frailty and Fall Assessment Questionnaire (FFAQ) which demonstrated 0.79 internal consistency. The IBM SPSS version 22 was used for statistical analysis. Frequency, percentage, odds ratio statistics and chi-square test were used for data analysis. Results were significant at p value ≤ 0.05. Results: Out of 500 eligible participants, 13 (2.6 %) declined and 11(2.2 %) provided biased answers. A total of 476(95.2 %) valid responses were analysed. The prevalence of frailty among elderly was 40.8 %, prefrailty 40.8 % and robust 18.5 %. Frailty, prefrailty and robust were associated with sex and education (p value < 0.05) while no association was observed with age (p value > 0.05). In the odds ratio analysis, frailty and prefrailty were positively correlated with education (OR≥1) while a negative correlation was observed with age (OR≤1) respectively. Conclusion: Approximately half of the elderly population is frail and prefrail, with less than one-quarter being robust. With the increase in the elderly population, the prevalence of frailty is expected to increase. Frailty is significantly associated and correlated with variables. Reliable community-based interventions with the combined efforts of professionals are crucial for reversing, preventing and managing frailty in the geriatric population.